Simultaneous Determination of Uric Acid and Xanthine Using a Poly(Methylene Blue) and Electrochemically Reduced Graphene Oxide Composite Film Modified Electrode - Gen Liu; Wei Ma; Yan Luo; Deng-ming Sun; Shuang Shao (Journal of Analytical Methods in Chemistry)
Poly(methylene blue) and electrochemically reduced graphene oxide composite film modified electrode (PMB-ERGO/GCE) was successfully fabricated by electropolymerization and was used for simultaneous determination of uric acid (UA) and xanthine (Xa). Based on the excellent electrocatalytic activity of PMB-ERGO/GCE, the electrochemical behaviors of UA and Xa were studied by cyclic voltammetry (CV) and square wave voltammetry (SWV). Two anodic sensitive peaks at 0.630 V (versus Ag/AgCl) for UA and 1.006 V (versus Ag/AgCl) for Xa were given by CV in pH 3.0 phosphate buffer. The calibration curves for UA and Xa were obtained in the range of 8.00 × 10−8~4.00 × 10−4 M and 1.00 × 10−7~4.00 × 10−4 M, respectively, by SWV. The detection limits for UA and Xa were 3.00×10-8 M and 5.00×10-8 M, respectively. Finally, the proposed method was applied to simultaneously determine UA and Xa in human urine with good selectivity and high sensitivity.